MODUS, MOTIF, TUJUAN, DAN FUNGSI UJARAN EKSPRESIF DALAM TEKS BERITA SIDANG KASUS PELANGGARAN PROTOKOL KESEHATAN COVID-19 - Muji Muji (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
Dishonorable expressive utterances within the news text of violating the COVID-19 health protocol are problematic because they harm other partners. This article points to talk about the mode, rationale, reason, and work of despicable expressive discourse within the setting of the COVID-19 health protocol. The research method is a qualitative research method, with a phenomenological type of research and data in expressive utterances that are indicated as despicable. Information was collected utilizing observation techniques, documentation studies, and focus group discussions (FGD). The data were analyzed using critical discourse analysis techniques adopted from Fairclough and Wadok. The comes about appeared that passed on the contemptible expressive mode of discourse by making fun of, contending, abhor discourse and inconsiderate discourse. The deliberate desire to win something drives the thought process for contemptible is considered all-powerful and has the back of other partners. The purpose of the expressive utterance of reproach is to kill the characters of other partners who are not in the same opinion and the utterance users use to achieve a specific power position.